2008
DOI: 10.1007/s11096-008-9204-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between methotrexate and omeprazole in an adolescent with leukemia: a case report

Abstract: We present a case of severe mucositis due to a drug-drug interaction between methotrexate (MTX) and omeprazole in an adolescent with Acute Lymphatic Leukemia (ALL). In view of the prevalence of MTX in many cytotoxic protocols, and the frequent use of omeprazole in the (ambulatory) oncology setting, we believe that this case-report is worth mentioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Recently, the delayed elimination of MTX associated with serious side effects was described in three retrospective clinical studies of patients treated with high doses of MTX and PPIs (Joerger et al, 2006;Suzuki et al, 2009;Santucci et al, 2010;Leveque et al, 2011) and one prospective study of low dose MTX (Vakily et al, 2005). Although conflicting data were reported in some case reports for either omeprazole or pantoprazole (Whelan et al, 1999;Beorlegui et al, 2000;Troger et al, 2002;Bauters et al, 2008), recent clinical studies are in line with our results suggesting that PPIs might decrease MTX renal clearance via OAT3-mediated inhibition. In the first study, Joerger et al (2006) described 76 patients who received high-dose MTX, 13 of whom received omeprazole or lansoprazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the delayed elimination of MTX associated with serious side effects was described in three retrospective clinical studies of patients treated with high doses of MTX and PPIs (Joerger et al, 2006;Suzuki et al, 2009;Santucci et al, 2010;Leveque et al, 2011) and one prospective study of low dose MTX (Vakily et al, 2005). Although conflicting data were reported in some case reports for either omeprazole or pantoprazole (Whelan et al, 1999;Beorlegui et al, 2000;Troger et al, 2002;Bauters et al, 2008), recent clinical studies are in line with our results suggesting that PPIs might decrease MTX renal clearance via OAT3-mediated inhibition. In the first study, Joerger et al (2006) described 76 patients who received high-dose MTX, 13 of whom received omeprazole or lansoprazole.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, several case reports in oncology (Reid et al, 1993;Beorlegui et al, 2000;Troger et al, 2002;Bauters et al, 2008) and two retrospective cohort studies (Suzuki et al, 2009;Santucci et al, 2010) have suggested that the coadministration of proton pump inhibitors (PPIs), including omeprazole, pantoprazole, lansoprazole, and rabeprazole, decreased the renal clearance of MTX. The elimination of MTX was significantly delayed during cycles with one PPI but normalized during subsequent cycles after PPI discontinuation or substitution with ranitidine.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-drug interaction with valaciclovir and fluoxetine treatment is unlikely due to their metabolism pathways and the lack of drug interaction reported in the literature. However, as it has already been described with other PPI, alteration in methotrexate renal elimination might be understood by drug interaction with pantoprazole [8,9,10,11]. In opposition with Whelan et al [24] who suggested that there was no alteration in plasma methotrexate clearance in a single patient treated with omeprazole, recent studies consistently showed that PPI coadministration could reduce methotrexate clearance, resulting in significantly higher plasma methotrexate concentrations [15,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Different elimination pathways of methotrexate and its main metabolite 7-hydroxymethotrexate are mediated by membrane cell transporters such as breast cancer resistance protein (BCRP), expressed on the apical membranes of renal epithelial cells, and hydrogen-potassium adenosine triphosphatase enzyme (H + /K + /ATPase pump) in the distal nephron [11,25,27]. A possible decrease in hepatobiliary elimination of high-dose methotrexate should also be taken into account because BCRP is present in the bile canalicular membrane of human liver hepatocytes [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation